Peran Religious Coping terhadap Emotional Well-Bieng pada Komunitas Dewasa Awal di Gereja "X" Semarang - Claudia Margaretha; Yuspendi Yuspendi; Maria Yuni Megarini Cahyono (Humanitas (Jurnal Psikologi), 2024)
This research aims to understand the religious coping strategies centered on the God that influence emotional well-being in the early adulthood group aged 18-45 years old. The research method used in this study is non-experimental by collecting data through the administration of religious coping and emotional well-being (EWB) questionnaires. The data obtained will be processed using multiple regression statistical tests on 68 people. The results showed a significant role of religious coping on emotional well-being. There is a significant simultaneous contribution of positive R-coping and negative R-coping to EWB. The path analysis results showed that both play a significant role to EWB. Based on simultaneous regression tests of positive    R-coping and negative R-coping on positive feelings and negative feelings, it is known that there is a significant role on positive feelings, but no significant role on negative feelings. This means that religious coping will play a significant role in EWB and if only on one feeling, then it will play a role in positive feelings rather than negative feelings. The suggestion that can be given is that the early adulthood group uses religious coping in developing a balance of positive and negative feelings (feelings balance) when interacting in the environment.